Optimization of VAWT installation with spatial and temporal complexity considerations - Alqahtani, Mohammed (Frontiers in Energy Research, 2024)
The constant need for fuel to meet the commercial sector’s ever-increasing demand has driven researchers to discover and optimize renewable energy resources, paving the way for sustainable production of reliable and clean energy resources. The goal of the current work is to close the gap in process parameter optimization needed to convert wind energy wake from traffic on highways into electrical energy utilizing vertical-axis wind turbines (VAWTs). The energy output from the VAWT is analyzed to investigate how it is impacted by the variations in multiple parameter settings. Using the central composite design (CCD), a three-level four-factor array was used to investigate the following parameters: VAWT vertical distance (VD) and horizontal distance (HD) as continuous parameters, while road side (S) and location (L) of VAWT as categorical parameters. To find the most important parameter, response surface methodology (RSM) optimization and an analysis of variance (ANOVA) test are performed. L accounts for 66.67% of the total variable, with S coming in second with 51.80%. Using the best results from RSM and ANOVA, a confirmation test is run, and the results show yields of 88.75% ± 0.05% and 87.5% ± 0.05%, respectively. Therefore, RSM and ANOVA can be utilized equally for optimization at the same VAWT design. Lastly, the findings of the economic and environmental evaluation demonstrate that, in comparison to the basic settings, VAWT operating at optimal settings can save up to 180% and 200% more energy and reduce carbon emissions, respectively.